Procedures For Sustainable Credit Disbursement In The Banking Sector In Realizing Justice - Redy Rahmad Samosir; Abdullah Sulaiman; Megawati Barthos (International Journal Labs, 2024)
This research explores sustainable lending procedures in the Indonesian banking sector, which is the key to fair and sustainable economic development. Based on Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking, as well as Law No. 21 of 2011 amended by Law No. 4 of 2023 concerning Development and Strengthening of the Financial Sector, this study explores the implementation of Financial Services Authority Regulation No. 51/POJK.03/2017. Using a qualitative approach, researchers inventory and analyze relevant legal materials to assess the effectiveness of sustainable lending. The research findings show that despite progress, improvements in supervision and risk management are still needed to ensure sustainable financial practices. This research proposes a credit distribution model that takes into account the principles of justice and sustainability, through strategic coordination between financial institutions, government, and other stakeholders to achieve appropriate economic development goals based on the 1954 Constitution